INFLUENCE OF MOTIVATION, LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION OF PT. X - FAUJIAH, CINDY; FARIDA, IDA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to examine the influence of motivation, leadership, and organizational culture on job satisfaction of Viscose department employees at PT. X. This research was conducted at PT. X. The research method used in this research is descriptive research and causal research. The sample of this study amounted to 147 employees, using non-probability sampling techniques. Data collection through distributing questionnaires. The data analysis technique used is multiple regression analysis. Based on this research conducted, the result showed that motivation, leadership, and organizational culture affect job satisfaction.